2011
DOI: 10.4103/0974-2077.85022
|View full text |Cite
|
Sign up to set email alerts
|

A study on the alterations in skin viscoelasticity before and after an intradermal administration of growth factor

Abstract: Background:While photo-aging is believed to be preventable by the complete blockage of ultraviolet rays, there is no epoch-making method except sing fillers or autologous fat injection, for rejuvenating the skin once it has aged.Objective:Our group developed a new method for rejuvenating aged skin by the direct intradermal injection of basic fibroblast growth factor, the first method of its kind in the world. In this paper we report the results of long-term follow-up observations and alterations in skin viscoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
(29 reference statements)
1
12
0
Order By: Relevance
“…This preliminary study demonstrates the functionality of Skin-meter and confirms that the measurements not are affected by the optical components of the circuitry with use of a specific probe, so the skin and area measurements are not invalidated by the presence of blood microcirculation of the subjects tested. Skin parameters are also easily detected and analysed, the data prove to be in agreement with results reported in previous studies [12,[14][15][16]. The method used may be effective in a specific way: only dermis portion of human skin is considered and this allows detecting the physiological requirements necessary to the human skin to not be compromised after training.…”
Section: Resultssupporting
confidence: 84%
“…This preliminary study demonstrates the functionality of Skin-meter and confirms that the measurements not are affected by the optical components of the circuitry with use of a specific probe, so the skin and area measurements are not invalidated by the presence of blood microcirculation of the subjects tested. Skin parameters are also easily detected and analysed, the data prove to be in agreement with results reported in previous studies [12,[14][15][16]. The method used may be effective in a specific way: only dermis portion of human skin is considered and this allows detecting the physiological requirements necessary to the human skin to not be compromised after training.…”
Section: Resultssupporting
confidence: 84%
“…The increase in these values may indicate a decrease in the viscosity of interstitial fluid as a result of increased water content and changes in the composition or structure of proteoglycans [8]. Other authors report that parameter R6 depends on skin hydration [9][10][11], while others have found that with ageing, changes in skin elasticity coefficient (R2, R7) are more pronounced than those in skin viscoelasticity (R6) [12,13]. Kruger et al report a high correlation between R2 and age, and a low one between R6 and age, and recommend that parameters R2 and R7 be used in the assessment of skin ageing [14].…”
Section: Discussionmentioning
confidence: 99%
“…This device has been utilized to assess a variety of clinical and basic science outcomes. From a clinical perspective, the Cutometer has been used to assess changes in skin elasticity after radiation therapy [10], CO 2 laser treatments [11], as well as assess the efficacy other proposed skin tightening methods [12]. From a basic science perspective, the device has the ability to quantify changes in elasticity as people age [8], changes based on hydration [3] as well as across body regions [13].…”
Section: Introductionmentioning
confidence: 99%